Optimizing well construction by establishing overpressure mechanism in Panna Formation, Western Offshore Basin, India. (December 2021) - Talreja, Rahul; Kumar, Rajeev; Kumar, Prince; Bhagat, Jayant; Bandyopadhyay, Bidesh; Bhuskute, Akshay; Singh, Amit Kumar
Abstract: The Panna Formation was deposited during the Paleocene period and is the oldest hydrocarbon-bearing tertiary sedimentary unit in the Western Offshore Basin (WOB). It is also believed to be the source rock above which hydrocarbons pools in. In the recent years, exploration activity in the Panna Formation has significantly increased, owing to its own potential hydrocarbon pools. The primary challenge encountered when drilling through the Panna Formation include well flows, mud losses, stuck pipe events, and limitation of using logging while drilling (LWD) tools due to high temperature which makes it tough for real-time monitoring without LWD. The stable-mud-weight window becomes narrow (<2 ppg), and the pore pressure seems to vary considerably from near-hydrostatic to ∼17.5ppg mud weight equivalent (EMW). This overpressure zone is correlated with relative thickness of Panna Formation and well locations in the region. The pore pressure ramp is observed to start either from the bottom of the Lower Bassein or Devgarh Formations (formation overlying Panna) or 120m–150 m inside the Panna Formation itself. Additionally, the transition of pore pressure from near-hydrostatic to overpressure zone is quite sudden. As a result, when the lithological seal isolating the high-pressure compartment is broken during drilling, well flow is encountered. In the process of well control, mud weight is increased to corresponding shut-in-drill-pipe pressure (SIDPP), which sometimes causes mud losses in the overlying formations because of insufficient fracture gradient. To delineate the area with overpressure and identify its mechanism, a comprehensive geomechanics study with lithology types has been carried out across 5 main blocks of WOB. The study integrates petrophysical, geological, and drilling information to give insight into the overpressure mechanism and safe drilling solutions through this complex setup. The pore pressure, rock mechanical properties, and stress profiles have been estimated in multiple wells to build robust geomechanical models and estimate the most stable mud weight windows. This study establishes the Type-II overpressure phenomenon with the help of crossplots between effective stress with velocity, density with compressional slowness, and pressure with porosity. There is a clear shift in the geothermal gradient associated with the overpressure interval. The casing policies for safe drilling have been discussed in different scenarios. The analysis has also outlined the occurrence of overpressure in triangular area adjacent to the Bombay High Oilfield.